수소제조시설 수증기 개질 공정에 대한 위험성평가 - 이종석 (The Graduate School, Ajou University, 2024)
In this study, risk assessment technique was applied to steam reforming process of hydrogen producing facilities to help use it as basic data for preparing safety measures at related workplaces. To this end, various risk assessment techniques (HAZOP, LOPA, CA) were applied, centering on the reforming process, which operates at the highest temperature and pressure among the entire processes, and obtained research results are summarized as follows._x000D_ Among a total of 27 accident scenarios in abnormal conditions identified in HAZOP, three scenarios of risk grade 2 or higher that require action were derived. Depending on leak size of the syngas outlet pipeline in the reforming process, the occurrence of Jet Fire, VCE, Flash Fire, was predicted. In addition, additional IPL was applied through LOPA analysis to prevent pipe rupture due to high temperature in the reformer process. In the case of applying combustible sensors and emergency blocking systems, mitigated frequency value was improved to 1.00E-5/yr. Also, applying fireproofing system (Water spray installation), mitigated frequency value was improved to 1.00E-4/yr. Through this, the risk acceptance criterion of 1.00E-4/yr was met._x000D_ As a result of predicting Jet Fire damage caused by 65 mm syngas pipe total failure at the rear end of the reformer, a flame length of up to 17.6 m was found based on radiant heat of 5 kW/m2. Also, VCE caused damage of up to 42.6 m at an overpressure of 0.07 bar (1 psi), and a Flash Fire had an impact range of about 12.7 m based on LFL (Lower Flammable Limit) of hydrogen._x000D_ Since this study evaluated the qualitative and quantitative risk assessment of general steam reforming process, it is believed that it will be helpful as basic data on the operation and design of related facilities.|본 연구에서는 수소제조시설의 수증기 개질 공정에 대해 위험성평가 기법을 적용하여 관련 사업장에서 안전대책을 수립하기 위한 기초자료로 활용하고자 하였다. 전체 공정 중 가장 고온, 고압으로 운전되는 개질공정 (Reforming)을 중심으로 위험 및 운전분석 기법 (HAZOP), 방호계층분석 기법 (LOPA), 사고 피해예측 기법 (CA)을 적용하였고, 얻어진 연구 결과를 요약하면 다음과 같다._x000D_ HAZOP 수행에서 확인된 총 27개의 비정상 상태의 사고시나리오 중에서 조치가 필요한 위험등급 2등급 이상의 시나리오 3가지를 도출하였다. 개질공정 (Reforming)에서 합성가스 (Syngas) 출구배관 (Outlet pipeline)의 누출 정도에 따라 제트화재 (Jet Fire), 증기운폭발 (VCE), 플래시화재 (Flash Fire) 등의 발생이 예측되었다. 또한, LOPA 분석을 통해 개질기 (Reformer) 공정의 고온에 의한 배관 파열 방지를 위해 추가적인 IPL을 적용했다. 가연성감지기 및 긴급차단 시스템을 적용할 경우 완화된 빈도값이 1.00E-5/yr까지, Fireproofing (Water spray installation) 을 적용할 경우 1.00E-4/yr까지 향상되었다. 이를 통해 위험허용기준인 1.00E-4/yr을 충족하였다._x000D_ 개질기 후단 65 mm Syngas 배관 파단 발생 시 누출에 의한 제트화재 피해예측 결과 5 kW/m2의 복사열을 기준으로 최대 17.6 m의 화염길이가 도출되었다. 증기운 폭발의 경우 0.07 bar (1 psi)의 과압에서 최대 42.6 m의 피해를, 플래시화재의 경우 수소의 연소하한계를 기준으로 약 12.7 m의 영향범위를 나타냈다._x000D_ 본 연구는 일반적인 수증기 개질 공정에 대한 정성 및 정량적 위험성평가로써 관련 설비의 운영, 설계에 대한 기초자료로 활용할 수 있을 것으로 사료된다.
학위논문(석사)--환경안전공학과,2024. 2
Keywords: CA; HAZOP; LOPA; 수소; 수증기 개질 공정; 위험성평가